Bridging Perception and Practice: How User Attitude Shapes EMR Utility, Convenience, and Self-Efficacy for Greater Adoption - Indrayani, Reka; Supriyantoro, Supriyantoro; Pamungkas, Rian Adi (International Journal of Nursing and Health Services (IJNHS), 2025)
Background: The implementation of Electronic Medical Records at the Tangerang Regency Hospital has been since September 2023, but in its implementation in November 2023 it has only reached 70.44%, the target set by the hospital is 100%, this is due to the actual use that is not optimal. Objective: The purpose of this study is to analyze the influence of perception of utility, perception of convenience, and self-efficacy on the actual use of electronic medical records through user attitudes as intervening variables in the Outpatient Installation of Tangerang Regency Hospital. Method: A cross-sectional study was applied in this study. The sample in this study totaled 83 with a sampling technique using the total sampling method. Data was obtained through questionnaires. Result: The results of the Path Coefficients hypothesis test, the results of t>1.96 and p<0.05 were obtained. The results of data analysis and direct hypothesis testing found that there was an influence on the perception of utility, perception of convenience, self-efficacy and user attitude towards actual use. Testing the indirect hypothesis found that there was an influence of the perception of utility, perception of convenience, and self-efficacy on actual use with the attitude of the user as a mediator. Conclusion: the attitude mediated the perception of utility, perception convenience, and self-efficacy on improving the actual usage EMR. Recommendation: the management of hospital need to consider all factors to implement the effective EMR